A Systematic Review of Misconceptions in Particle Dynamics: Identification, Causes, and Remediation - Muhammad Faldi Maliqi; Emiliannur Emiliannur; Festiyed Festiyed; Hayyu Yumna (Department of Physics Universitas Negeri Padang, 2026)
Particle dynamics is a foundational branch of physics, yet students frequently struggle with abstract concepts, leading to persistent misconceptions that hinder scientific reasoning. This study aims to analyze the specific concepts prone to misconceptions in particle dynamics, identify their primary causes, and evaluate the effectiveness of various remediation strategies to improve conceptual understanding. This research employed a descriptive quantitative design using the Systematic Review method following the PRISMA 2020 guidelines. A total of 20 scientific articles published between 2020 and 2025, indexed in national and international databases, were analyzed. The study integrated a bibliometric approach using VOSviewer software to visualize research trends and keyword networks, ensuring a robust and objective synthesis of the current literature. The findings indicate that misconceptions are most prevalent in Newton’s Laws (45%), followed by the Law of Conservation of Momentum (35%), and force and net force (30%). The primary cause of these errors is students' internal prior conceptions (65%), often derived from intuitive daily experiences that conflict with scientific principles. Effective remediation strategies identified include active learning models such as guided inquiry, generative learning, and cognitive conflict approaches. Furthermore, the integration of interactive simulations like PhET and E-LKPD significantly enhanced the remediation process by providing essential visual scaffolding. Misconceptions in particle dynamics remain a major challenge, predominantly rooted in intuitive reasoning regarding force and motion. Successful remediation requires pedagogical shifts toward active student involvement and the use of technology-based visualizations to facilitate conceptual change. These results provide a vital scientific reference for educators to design targeted interventions and for curriculum developers to address conceptual gaps early in physics education.